The role of price, service quality, and ease of use in determining customer loyalty - Hidayat, Yusri; Yolanda, Mike; Fasyni, Awisal (Marketing Management Studies, 2023)
This study aims to analyze the effect of price, service quality, ease of use on loyalty with satisfaction and trust as intervening variables of maxim services in Padang City. While the number of samples in this study were 130 respondents. Data was collected through distributing questionnaires directly via google form and data processing was carried out through Smart PLS software. The results of this study indicate that: (1) Price has a significant effect on maximal user loyalty in Padang City, (2) Service Quality has a significant effect on maximal user loyalty in Padang City, (3) Ease of Use has a significant effect on maxim user loyalty in Padang City, (4) Satisfaction has a significant effect on maxim user loyalty in Padang City, (5) Trust has a significant effect on maxim user loyalty in Padang City, (6) Price has a significant effect on maxim user Satisfaction in Padang City, (7) Service Quality has a significant effect on maxim user Satisfaction in Padang City, (8) Service Quality has a significant effect on maxim user Trust in Padang City, (9) Ease of Use has a significant effect on maxim user satisfaction in Padang City, (10) Price has a significant effect on loyalty through satisfaction as an intervening variable for maxim users in Padang City, (11) Service Quality has a significant effect on loyalty through satisfaction as an intervening variable for maxim users in Padang City, (12) Service Quality has a significant effect on loyalty through trust as an intervening variable for maxim users in Padang City, (13) Ease of Use has a significant effect on loyalty through satisfaction as an intervening variable for maxim users in Padang City.